2008
DOI: 10.1529/biophysj.107.117697
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Temperature-Dependent Heat Capacity Changes in Protein-DNA Interactions

Abstract: A large, negative DeltaCp of DNA binding is a thermodynamic property of the majority of sequence-specific DNA-protein interactions, and a common, but not universal property of non-sequence-specific DNA binding. In a recent study of the binding of Taq polymerase to DNA, we showed that both the full-length polymerase and its "Klentaq" large fragment bind to primed-template DNA with significant negative heat capacities. Herein, we have extended this analysis by analyzing this data for temperature-variable heat ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 53 publications
5
23
0
3
Order By: Relevance
“…The stoichiometry obtained by ITC for this specific association is 1.1, consistent with a binding involving one palindromic DNA sequence per Mtb -HigA1 dimer present in the Mtb -SecB TA /HigA1 hetero-hexamer. Measuring the temperature dependence of the enthalpy gave a negative heat capacity of binding (−1.3 kJ mol −1 K −1 ) as typically reported for the majority of sequence-specific protein/DNA associations 43 . Together these results show that the highly unstable Mtb -HigA1 antitoxin can form a functional dimer following binding to its specific chaperone partner.…”
Section: Resultssupporting
confidence: 57%
“…The stoichiometry obtained by ITC for this specific association is 1.1, consistent with a binding involving one palindromic DNA sequence per Mtb -HigA1 dimer present in the Mtb -SecB TA /HigA1 hetero-hexamer. Measuring the temperature dependence of the enthalpy gave a negative heat capacity of binding (−1.3 kJ mol −1 K −1 ) as typically reported for the majority of sequence-specific protein/DNA associations 43 . Together these results show that the highly unstable Mtb -HigA1 antitoxin can form a functional dimer following binding to its specific chaperone partner.…”
Section: Resultssupporting
confidence: 57%
“…We and others have strongly suggested that these correlations may hold for some subset of protein-DNA interactions, but that neither correlation holds quantitatively for DNA-protein interactions in general (29,30). As a general indicator, DC p is definitely reflective of some DASA nonpolar in protein-DNA interactions, but exact quantitative correlation does not universally hold for any current model for this specific class of interactions (29,30).…”
Section: Enthalpies and Heat Capacities Of Binding Of Different Dna Smentioning
confidence: 85%
“…Finally, over 40 % of E. coli's transcription factors are negatively autoregulated [55] and the formation of many protein-DNA complexes exhibits a non-linear temperature-dependence [56]. Negative autoregulation can thus play an important role in maintaining a linear response in the regulation of downstream genes [57] upon changes in environmental variables, such as temperature, affecting the activity of a DNA-binding protein.…”
Section: Autoregulation and The Temperature-dependence Of Dnaa-dna Inmentioning
confidence: 99%